Environmental and Management Factors Affecting the Time Budgets of Free-Ranging Iberian Pigs Reared in Spain - Míriam Martínez-Macipe; Eva Mainau; Xavier Manteca; Antoni Dalmau (Animals, 2020)
Understanding the natural behaviour of pigs in free-range conditions facilitates interpretation of their behaviour in intensive conditions. Studying six different farms over two years at different seasons, with climatic and management variations, allowed for a general description of Iberian pig behaviour and which factors have an influence on it. The main activity found was resting (56.5% of the time observed), followed by exploratory behaviour. However, this exploratory behaviour was higher when animals were fed only with natural resources than when fed with concentrates (50% versus 17.8%, respectively). In addition, pigs used bathing areas in summer that were not visited in winter. Negative social behaviour was seen more frequently than positive social behaviour, accounting, in total, for 1% of the total activity of animals. Pigs situated at the centre of the groups tended to remain more relaxed, while the peripheral animals remained more alert and vigilant. Our results indicate that foraging behaviour accounts for a significant proportion of pigs’ active time, but this proportion is much more reduced when pigs are fed concentrates. Therefore, behavioural needs in pigs reared in intensive conditions should consider that exploratory behaviour is reduced when pigs are fed with concentrates.